2013
DOI: 10.3791/50331
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Imaging of Nociceptive Intraepidermal Nerve Fibers in Human Skin Biopsies

Abstract: A punch biopsy of the skin is commonly used to quantify intraepidermal nerve fiber densities (IENFD) for the diagnosis of peripheral polyneuropathy 1,2 . At present, it is common practice to collect 3 mm skin biopsies from the distal leg (DL) and the proximal thigh (PT) for the evaluation of length-dependent polyneuropathies 3 . However, due to the multidirectional nature of IENFs, it is challenging to examine overlapping nerve structures through the analysis of two-dimensional (2D) imaging. Alternatively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
1
1
Order By: Relevance
“…Nevertheless, cannulation on the dorsum of the hand was thought to be more painful compared to the antecubital fossa due to the tougher skin and greater density of nociceptors on this site. 6,23,24 However, this study showed the opposite results while suggesting insertion of a PIVC on the dorsum of the hand in an effort to minimize pain during the procedure. Nevertheless, the risk for accidental removal and occlusion seems to be higher on the dorsum of the hand, as concluded by the trial of Wallis et al 25 To add to this, Bregenzer et al 26 even showed a higher incidence of PIVC obstruction in patients with a PIVC inserted on the dorsum of the hand compared to other cannulation sites on the upper extremity.…”
Section: Discussioncontrasting
confidence: 54%
“…Nevertheless, cannulation on the dorsum of the hand was thought to be more painful compared to the antecubital fossa due to the tougher skin and greater density of nociceptors on this site. 6,23,24 However, this study showed the opposite results while suggesting insertion of a PIVC on the dorsum of the hand in an effort to minimize pain during the procedure. Nevertheless, the risk for accidental removal and occlusion seems to be higher on the dorsum of the hand, as concluded by the trial of Wallis et al 25 To add to this, Bregenzer et al 26 even showed a higher incidence of PIVC obstruction in patients with a PIVC inserted on the dorsum of the hand compared to other cannulation sites on the upper extremity.…”
Section: Discussioncontrasting
confidence: 54%
“…Assessment of the pain scores of the 28 patients who found the ACF to be a less painful site for cannula insertion showed that there was a difference of no more than one point in 17.85% of cases, which would suggest that not only did patients find cannulation in the dorsum painful more frequently, but also that it produced a greater difference. Reasons for the difference between the two sites are uncertain but may include tougher skin and greater density of nociceptors[ 5 6 ] on the DOH. While the results of this study validate the clinical practice of selection of the ACF in an effort to minimise pain of cannula insertion, it remains to be seen whether it should be chosen as the optimal site for venous cannulation in view of the aforementioned drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…The afferent nociceptive nerve fibers located in human muscle respond to mechanical and chemical stimuli [462]. Finally, focusing on skin, in human biopsies, researchers reported nociceptive intraepidermal nerve fibers [463][464][465] and rat and mice skin biopsies revealed intraepidermal free nerve fiber endings identified as afferent nociceptive fibers [466][467][468][469][470]. These evidences indicates that nociceptors or nociceptive afferent fibers are located in most body tissues and organs and, therefore, the substances released by adipose tissue that accumulate in these tissues and organs in obese subjects can interact with the nociceptors, causing their depolarization or their sensitization; thus, developing pain signals.…”
Section: Obesity and Pain: Crosstalk Between Adipose Tissue And Nocic...mentioning
confidence: 99%